Competencies of Indonesian Architects with Sosio Cultural Ecology: Anatomy based on Architect Background - Wijaksono, Sigit; ., Sasmoko; Indrianti, Yasinta; Anindyo Wid, Samuel (International Journal of Engineering and Technology, 2018)
The architect’s background becomes a key factor determining its success which is reflected through the competence of the architect itself. And the diversity of architectural backgrounds provided the basis for this research. The study aims to see if there are differences in the competence of Indonesian architects if distinguished based on demographic background and architectural work, and what architect’s background is the most powerful in determining its competence. A neuroresearch method is a method applied in this research. The results showed that there are differences in the competence of Indonesian architects if differentiated based on demographic background and architectural works. The second research result is the number of projects handled by Architects is a very decisive variable to realize the Indonesian architects become more competent. Â Â